A proposed digitization plan for archival materials at the University of the Philippines Diliman University Archives and Records Division - Tan, Marie Eugenie B. (School of Library and Information Studies, University of the Philippines Diliman, 2001)
The foremost aim of the study was to come up with a digitization plan specially catered to the preservation needs of the University Archives and Records Division of the University of the Philippines Diliman Main Library. The study was conducted in order to provide the UARD with an alternative to their preservation practices.